Facebook: A Versatile Platform for Blended Learning - Wong, Ling Shing; Wan, Betty Voon Niu (Asian Economic and Social Society, 2013)
Facebook is a popular networking tool among the young learners. This paper reports a practical usage of Facebook to engage learners in blended learning. The practical usage of Facebook in hosting online forums, sharing media files in vodcast, building collaborative content through Facebook Doc, and using Facebook as repository for articles and lecture notes has been described. Recent survey on 55 students revealed that a strong majority of the students agreed that Facebook has positive impact in their studies. Thus, the authors strongly recommend that Facebook can be used as an alternative tool to engage learners online